2019
DOI: 10.2106/jbjs.rvw.18.00139
|View full text |Cite
|
Sign up to set email alerts
|

Knee Arthroscopy for the Treatment of Lipoma Arborescens

Abstract: Background: Lipoma arborescens is a rare, intra-articular benign lesion characterized by hyperplastic formation of villous projections that commonly presents as nonspecific mechanical knee pain. The treatment of choice for lipoma arborescens of the knee is open or arthroscopic synovectomy. However, data are lacking on the success of arthroscopic treatment, despite its increasingly widespread use. We aimed to systemically review the outcomes of arthroscopic treatment of lipoma arborescens.Methods: PubMed and Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…According to a systematic review about the treatment of LA in the knee, gold standard treatment is arthroscopic synovectomy with a success rate exceeding 95%. [ 14 ] Evidences for LA treatment of the elbow joint are insufficient but it is safe to assume that an arthroscopic approach is also the most effective.…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review about the treatment of LA in the knee, gold standard treatment is arthroscopic synovectomy with a success rate exceeding 95%. [ 14 ] Evidences for LA treatment of the elbow joint are insufficient but it is safe to assume that an arthroscopic approach is also the most effective.…”
Section: Discussionmentioning
confidence: 99%
“…Excision and synovectomy of the affected joint have been proposed as a treatment option. Both open and arthroscopic techniques have been reported, leading to good short-term functional results without recurrences [ 5 , 15 ]. According to this systematic review, one-stage open or arthroscopic procedures address both LA and potential concurrent pathologies, such as rotator cuff or labral tears, and should be considered as standard treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether lesion size and location may play a role in determining specific approaches. A systematic review on the arthroscopic treatment of LA of the knee revealed a satisfactory short-term outcome [ 15 ]. The present study supports similar findings: patients may benefit from less invasive arthroscopic procedures when feasible, as arthroscopic treatment of shoulder [ 2 , 3 , 28 , 35 , 36 ] and elbow lesions [ 13 ] led to promising short-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This surgical approach obtains good clinical outcomes with a low recurrence rate of 2.8%, suggesting it should be the first-line surgical intervention. 44 In the setting of secondary lipoma arborescens, the inciting process should also be addressed at the time of surgery, if possible, to limit disease recurrence. 45 There are limited data surrounding outcomes of patients undergoing TKA in the setting of lipoma arborescens.…”
Section: Lipoma Arborescensmentioning
confidence: 99%